BIOCHEMICAL MARKERS OF OXIDATIVE STRESS PATHWAYS IN MAJOR DEPRESSION - Syed Shabbar Masih (Journal of Biomedical and Pharmaceutical Research, 2021)
BACKGROUND: Depression affects 12% of people worldwide throughout the course of their lifetime. Depression is one of the most significant contributors among the 11% of Disability Adjusted Life Years caused by neuro-psychiatric illnesses. Despite so, there are up to 16 suicides per 100,000 people who suffer from depression. When depressed individuals are given the current standard medication therapy, which primarily targets 5-HT receptors, less than two thirds of them experience remission. Despite substantial research in this field, the current theories about major depression do not adequately explain the precise aetiology and character of depression. The pathophysiology of depression now appears to be heavily influenced by inflammation and neurodegeneration. Inflammation, autoimmune tissue damage, and persistent psychological stress all contribute to oxidative stress, which is a significant cause of serious depression. AIM: The aim of this study was to know the association of free radicals and anti-oxidant status in subjects suffering from major depression. MATERIAL AND METHOD: The Department of Biochemistry conducted this case-control study. The study comprised 60 major depressive disorder patients that were brand-new and drug-free, as determined by the consultant psychiatrist using the DSM IV. 30 healthy control volunteers who were matched for age and sex and were drawn from the public population made up the control group. None of the patients used or were dependent on alcohol, cigarettes, or any other substance. All of the healthy, non-diabetic, normotensive, tobacco- or alcohol-dependent control subjects included for the study also lacked any signs of acute or chronic infection. RESULTS: The case population consisted of 50 patients, 20 of whom were male and 30 of whom were female. Among the 50 patients, 35 were from urban backgrounds and 15 from rural ones. Regarding marital status, there were 10 single people and 40 married people, of which 1 was a widow and 1 was divorced. Age and gender between depressed patients, first-degree relatives, and controls did not differ significantly. While the mean plasma levels of nitrite were lower in cases than in controls, this difference was not statistically significant, and the mean plasma levels of MDA were considerably greater in cases as compared to the control group. Despite the fact that patients had lower mean plasma ceruloplasmin levels than controls, these differences were statistically insignificant. Malondialdehyde and ascorbic acid were discovered to be connected on an inverse regression analysis after all parameters had been assessed for the regression analysis. CONCLUSION: The pathophysiology of depression may involve oxidative stress. This indicates that oxidative stress is a well-recognized result and is evident in samples from a range of demographic groups. It is unknown how far this discovery may be applied to improve clinical outcomes. The current study was cross-sectional; the patient group’s biochemical parameter values following treatment could have improved the study’s usefulness. KEYWORDS: Malondialdehyde, Major depression, Nitric oxide, Reactive Oxygen Species, Super oxide dismutase; Nitric oxide and Oxidative stress